2020
DOI: 10.1002/app.49917
|View full text |Cite
|
Sign up to set email alerts
|

Rheological/thermal properties of poly(ethylene terephthalate) modified by chain extenders of pyromellitic dianhydride and pentaerythritol

Abstract: Due to low molecular weight and wide molecular weight distribution, polyethylene terephthalate (PET) shows weak melt strength properties. In this study, the synergistic effect of using different types of chain extenders and catalyst on rheological behavior of PET has been investigated. Long-chain branching is known as a suitable method for developing the structure of PET during reactive melt processing. Thus, pyromellitic dianhydride (PMDA) and pentaerythritol (PENTA) were added to the fiber grade PET. The bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 70 publications
(176 reference statements)
0
21
0
Order By: Relevance
“…The effect of pyromellitic dianhydride (PMDA), as the most commonly used chain extender, on the properties of PET has been comprehensively investigated. 32 34 Incorporation of PMDA significantly decreases the carboxyl content, increases the intrinsic melt viscosity, and improves its rheological behavior. These properties are associated with increased molecular weight (MW) and chain entanglement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pyromellitic dianhydride (PMDA), as the most commonly used chain extender, on the properties of PET has been comprehensively investigated. 32 34 Incorporation of PMDA significantly decreases the carboxyl content, increases the intrinsic melt viscosity, and improves its rheological behavior. These properties are associated with increased molecular weight (MW) and chain entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of chain extenders by adding reactive functional groups, including trimethyl trimellitate, isocyanates, epoxy-based compounds, bis-oxazolines, and organic phosphites are effective at increasing intrinsic viscosity, molecular mass, and melt strength. The effect of pyromellitic dianhydride (PMDA), as the most commonly used chain extender, on the properties of PET has been comprehensively investigated. Incorporation of PMDA significantly decreases the carboxyl content, increases the intrinsic melt viscosity, and improves its rheological behavior. These properties are associated with increased molecular weight (MW) and chain entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Dolatshah et al demonstrated that DBTDL may operate as an accelerator of the interaction between PET and PMDA, as well as PENTA, enhancing the chain extension rate and improving rheological characteristics in lower time. [ 55 ] Hanley et al obtained similar results for branching and chain extension of PET chains employing PMDA and PENTA as chain extenders. They showed that with raising the content of chain extender, weight average molecular weight (Mw), molecular weight range, and apparent viscosity increased considerably, while number average molecular weight (Mn) was almost constant and MFI got decreased.…”
Section: Introductionmentioning
confidence: 77%
“…Reaction of polyethylene terephthalate (PET) and: (A) pyromellitic dianhydride (PMDA), (B) pentaerythriol (PENTA), (C) PMDA, and PENTA [ 55 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation